ASME 2009 InterPACK Conference, Volume 2 2009
DOI: 10.1115/interpack2009-89134
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Temperature Measurements Near the Contact Line of an Evaporating Thin Film in a V-Groove

Abstract: Thin-film evaporation of heptane in a V-groove geometry is experimentally investigated. The groove is made of fused quartz, and electrical heating of a thin layer of titanium coated on the backside of the quartz substrate provides a constant heat flux. The effects of liquid feeding rate on the temperature suppression in the thin-film region and on the meniscus shape are explored. High resolution (∼6.3 μm) infrared thermography is employed to investigate the temperature profile in the thin-film region, while a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…We have previously shown that a 50 μm region near the contact line of an evaporating meniscus contributes to as much as 50−70% of the total heat transfer from the meniscus depending on the heat flux and geometrical details. , These results were based on thermal analysis carried out on the basis of microscale infrared temperature measurements obtained in the region of the contact line. The infrared transparency of an 80 μm thick heptane film was exploited in these measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that a 50 μm region near the contact line of an evaporating meniscus contributes to as much as 50−70% of the total heat transfer from the meniscus depending on the heat flux and geometrical details. , These results were based on thermal analysis carried out on the basis of microscale infrared temperature measurements obtained in the region of the contact line. The infrared transparency of an 80 μm thick heptane film was exploited in these measurements.…”
Section: Resultsmentioning
confidence: 99%
“…A model developed by Wang et al showed that 8% of the heat transfer takes place from the thin-film region (0.16 μm long), but as much as 60% of the overall heat transfer takes place from a 5 μm long region. While all the above studies were conducted under saturated vapor conditions, more recently we have shown , that, in systems that are open to air, a 50 μm long region near the contact line contributes to nearly 50−70% of the heat transfer from an evaporating meniscus. It is to be noted that none of the above studies had access to local velocity measurements to quantify the evaporative mass loss in the thin-film region.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations have compared the heat transfer performance of different microstructures for thin film evaporation [16]. Meanwhile, various experimental approaches have been used to study the relation between meniscus shape and heat transfer behavior, such as infrared [17], and interference imaging [18]. However, these previous experimental investigations were generally steady state or slowly varying measurements where a constant heat flux was applied and a steady-state temperature was measured.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of researches have been devoted in various areas including heat transfer (Ward and Duan 2004;Wang et al 2005;Suman 2008; Ranjan et al 2009), material (Nguyen andStebe 2002;Truskett and Stebe 2003;Uchiyama et al 2010), etc. In recent years with the development of the micro-fabrication techniques, Marangoni convections in micro channels and their potential applications in microfluidic controls and electronic cooling have been more and more attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Ranjan et al (2009) numerically accounted the importance of the Marangoni effect in micro-scale heat transfer enhancement. Migliaccio et al (2009) and Wang et al (2010) discussed the Marangoni convections in V-groove channels for electronic cooling. The Marangoni convection was found playing important roles in determining the temperature distribution and the flow patterns.…”
Section: Introductionmentioning
confidence: 99%